Cortical thickness abnormalities in patients with first episode psychosis: a meta-analysis of psychoradiologic studies and replication in an independent sample. Issue 4 (15th December 2021) - Wen, Keren; Zhao, Youjin; Gong, Qiyong; Zhu, Ziyu; Li, Qian; Pan, Nanfang; Fu, Shiqin; Radua, Joaquim; Vieta, Eduard; Kumar, Poornima; Kemp, Graham J; Biswal, Bharat B
Abstract: Background: Abnormalities of cortical thickness (CTh) in patients with their first episode psychosis (FEP) have been frequently reported, but findings are inconsistent. Objective: To define the most consistent CTh changes in patients with FEP by meta-analysis of published whole-brain studies. Methods: The meta-analysis used seed-based d mapping (SDM) software to obtain the most prominent regional CTh changes in FEP, and meta-regression analyses to explore the effects of demographics and clinical characteristics. The meta-analysis results were verified in an independent sample of 142 FEP patients and 142 age- and sex-matched healthy controls (HCs), using both a vertex-wise and a region of interest analysis, with multiple comparisons correction. Results: The meta-analysis identified lower CTh in the right middle temporal cortex (MTC) extending to superior temporal cortex (STC), insula, and anterior cingulate cortex (ACC) in FEP compared with HCs. No significant correlations were identified between CTh alterations and demographic or clinical variables. These results were replicated in the independent dataset analysis. Conclusion: This study identifies a robust pattern of cortical abnormalities in FEP and extends understanding of gray matter abnormalities and pathological mechanisms in FEP.